2018
DOI: 10.1016/j.nicl.2017.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Age-related functional brain changes in FMR1 premutation carriers

Abstract: The FMR1 premutation confers a 40–60% risk for males of developing a neurodegenerative disease called the Fragile X-associated Tremor Ataxia Syndrome (FXTAS). FXTAS is a late-onset disease that primarily involves progressive symptoms of tremor and ataxia, as well as cognitive decline that can develop into dementia in some patients. At present, it is not clear whether changes to brain function are detectable in motor regions prior to the onset of frank symptomatology. The present study therefore aimed to utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Reduced activation of extrastriate cortex in premutation carriers may reflect difficulties attending to and processing basic visual input during rapid motor action. These findings extend the one known prior fMRI study of motor behavior in premutation carriers to indicate that decreased modulation of precision motor behavior in premutation carriers is associated with reduced processing of sensory feedback information ( Brown et al, 2018 ). We also found that extrastriate functional differences in premutation carriers were age-dependent; increased age was associated with increased extrastriate activation in premutation carriers, but reduced extrastriate activation in controls.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Reduced activation of extrastriate cortex in premutation carriers may reflect difficulties attending to and processing basic visual input during rapid motor action. These findings extend the one known prior fMRI study of motor behavior in premutation carriers to indicate that decreased modulation of precision motor behavior in premutation carriers is associated with reduced processing of sensory feedback information ( Brown et al, 2018 ). We also found that extrastriate functional differences in premutation carriers were age-dependent; increased age was associated with increased extrastriate activation in premutation carriers, but reduced extrastriate activation in controls.…”
Section: Discussionsupporting
confidence: 83%
“…Although sensorimotor deficits are frequently observed in premutation carriers with and without FXTAS, only one known task-based functional MRI study has investigated sensorimotor control in aging premutation carriers. Brown and colleagues reported reduced activation in cerebellar lobules V-VI in asymptomatic premutation carriers during visually-guided sequential finger tapping ( Brown et al, 2018 ). These findings suggest cerebellar dysfunction during manual motor behavior may represent a quantifiable trait dimension associated with atypical aging in premutation carriers and putative FXTAS risk.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, brain function is also affected by FMR1 premutation status in relatively young premutation carriers without FXTAS who demonstrate no overt neurological symptoms (5,6,9,11). Contrary to movementrelated neurodegeneration, which increases over time, emotional symptoms seem to be consistent over the lifespan in FMR1 premutation carriers; suggesting a neurodevelopmental origin, different from the neurodegeneration seen in FXTAS (7,11,19).…”
Section: Discussionmentioning
confidence: 96%
“…A growing body of research suggests that deterioration of frontal-cerebellar circuits is especially sensitive to the FMR1 premutation and appear to impact both control of movement (ataxia and tremor) and executive control of cognition (eg, working memory) in PC. 9,19,[33][34][35] For example, we previously showed that compared with HC, PC with and without FXTAS performing a verbal working memory EF task showed reduced activation in the right ventral inferior frontal cortex and left premotor/dorsal inferior frontal cortex. 9 In a cross-sectional structural brain imaging study of 322 males from age 8 to 81, we discovered that compared to age-matched HC, PC without FXTAS showed significantly accelerated age-related volume decreases in the cerebellum and brainstem and increased ventricular volume.…”
Section: Discussionmentioning
confidence: 99%